The use of nootropic drugs by higher education students to improve academic performance - Forte, Sérgio Alexandre Barreira (2023)
Studies on the use of drugs to improve attention and the learning of cognitive enhancements by university students have been developed in several countries, most notably the United States, Germany and England. However, in Brazil, studies still need to advance, since the increased use of these activators has different implications for the health of students, especially after dissemination on social networks. This research aims to verify the state of the art of the use of nootropic drugs by higher education students. The research methodology, descriptive and qualitative review type, was carried out based on national and international academic literature, using the content analysis technique, under the motivation, prevalence and implications categories of use. It was concluded that there is an increase in the use of nootropic drugs by university students and that the indiscriminate use can cause damage to health, as well as there should be a more intensified attention by educational institutions and public authorities.